DETECTION ANALYSIS ON FRAUDULENT FINANCIAL REPORTING USING FRAUD SCORE MODEL - Irawan, Puput Ade; Susilowati, Dewi; Puspasari, Novita (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2019)
This study aims to examine the elements of fraud in the fraud diamond theory. Fraud is proxied by seven variables consisting of three pressure elements namely financial target, financial stability, external pressure, two variables of opportunity element, namely effective monitoring and nature of industry, one variable from the rationalization element, namely change in auditor, one variable from capability element namely change in directors, which is hypothesized to affect financial statements fraud. This study uses earnings management to see the potential for fraudulent financial statements. Earning management is measured using the F-Score indicator. The research sample was selected using a purposive sampling method from 30 manufacturing companies and a research period of 5 years to obtain the number of sample units of 155 data which is listed on the Indonesia Stock Exchange (IDX) for the period of 2013 to 2017. The hypothesis testing used a multiple regression analysis model using SPSS 23. The results of the study indicate that financial targets and changes in auditor financial stability have a significant positive effect on fraudulent financial statements. While external pressure, effective monitoring, nature of industry, financial stability, change of directors, have no effect on financial statements fraud.